THE CHARACTERISTIC OF VEGETABLE ICE CREAM FROM SOY MILK BY THE ADDITION OF SWEET POTATOES PURPLE (Ipomoea batatas Poir) - Meme, Mega; Priyono, Suko; Mayasari, Eva (Jurnal Sains Pertanian Equator, 2019)
This research was aimed to determine the best characteristic of vegetable ice cream from soy milk by purple sweet potatoes juice. The experiment was designed using Randomized Block Design (RBD). The combination between soy milk and the sweet potatoes purple (0:85% 12:85% ; 23:85% ; 34:85% ; 46:85%) was composed as facor each combination was replicated four times. The data analyzed statistically using Anova (5%) and Tukey Test (5%). The best treatment determined using effectiveness index. The combination of soy milk and purple sweet potatoes 12:74%. is the best result were produced of fat content 3,14%, total dissolved solids 16.90brix, protein content 2.59%. high-speed melting (728 second) overrun 47.4%, and hedonic value of aroma 4.64 (like), taste 4.32 (slightly like), color 4.6 (like), texture 4.48 (slightly like).